The Influence of Sleman City Hall on Housing Price: A Case Study using OLX Data - Muhammad Naurul Muna; Romi Bhakti Hartarto; Ibnu Hajar (Universitas Muhammadiyah Ponorogo, 2023)
The Special Region of Yogyakarta (DIY) is one of the provinces in Indonesia with rapid development. This is indicated by the increasing number of shopping centers and the development of tourism and educational activities. Sleman Regency is a business center in DIY Province because it has the largest number of shopping centers in DIY Province compared to other districts. This study aims to determine whether the house adjacent to Sleman City Hall, the largest shopping center in Sleman Regency, has a higher selling price. While similar studies use primary data collected in the field through questionnaires, this study contributes to the property economics literature by utilizing secondary data from the OLX dataset to estimate the selling price of the house. A total of 229 data obtained through the OLX website related to selling prices, proximity to Sleman City Hall, and property characteristics were processed using multiple regression analysis with the ordinary least squares (OLS) technique. The finding of this study is that the distance from Sleman City Hall has a negative and significant effect on the selling price of the house. Another finding from this study is that the building area and land area have a positive and significant effect on the selling price of the house. On the other hand, the distance to the asphalt road has nothing to do with the selling price of the house.